Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah Terhadap Kinerja Guru di SMK Negeri 2 Siatas Barita - Medi Wagi Berutu; Lasmaria Lumban Tobing; Rogate A.T Gultom (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine the influence of the principal's leadership style on teacher performance at SMK Negeri 2 Siatas Barita in 2023. The method used in this research is a quantitative method with inferential statistics. The population is all 64 teachers at SMP Negeri 4 Pollung and this research is a population study. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the principal's democratic leadership style on teacher performance at SMK Negeri 2 Siatas Barita in 2023: 1) Test the analysis requirements: a) test the positive influence, the value of rxy = 0.594 > rtable(=0) .05,n=64) = 0.244, thus it is known that there is a positive influence between variable )= 2,000, thus there is a significant relationship between variable X and variable Y. 2) Effect test: uyu88. a) Test the regression equation, obtained the regression equation Y ̂="25.138"+0.511X. b) Regression coefficient of determination test (r2) = 35.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 33.721 > 4.00. Thus Ha is accepted and H0 is rejected.